2005
DOI: 10.1038/nn1384
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale changes in dendritic structure during reorganization of adult somatosensory cortex

Abstract: In adult rat somatosensory cortex (S1), neurons are biased and have less dendritic arbor close to the border between the forepaw and lower jaw representations. Changes in sensory experience cause changes in the functional organization of the neocortex. Therefore, we examined the morphology of neurons in the reorganized region of S1 after forepaw denervation. We found that during reorganization dendritic arbors changed to reflect the new location of the border.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 15 publications
5
57
1
Order By: Relevance
“…Although previous histologic and acute imaging studies have shown that sensory deprivation or stroke can alter the overall appearance of mature dendrites (Brown et al, 2007;Hickmott and Steen, 2005;Tailby et al, 2005), direct time-lapse images, showing the process by which these structures change, are lacking. Therefore, we analyzed changes in the length of each dendritic branch tip over time and grouped each one according to their location relative to the infarct (four groups, see Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous histologic and acute imaging studies have shown that sensory deprivation or stroke can alter the overall appearance of mature dendrites (Brown et al, 2007;Hickmott and Steen, 2005;Tailby et al, 2005), direct time-lapse images, showing the process by which these structures change, are lacking. Therefore, we analyzed changes in the length of each dendritic branch tip over time and grouped each one according to their location relative to the infarct (four groups, see Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To date, few studies have reported large-scale changes in the structure of mature dendritic arbors (particularly the apical tree), although histologic studies have reported changes in basilar dendrite complexity and orientation in response to enriched environments (Wallace et al, 1992), sensory deprivation (Hickmott and Steen, 2005;Tailby et al, 2005), and stroke (Biernaskie and Corbett, 2001;Gonzalez and Kolb, 2003;Jones and Schallert, 1992). One potential limitation of previous studies has been that they relied on static images of the neuronal structure (using Golgi-Cox staining or ex vivo filling of neurons) to estimate the dynamic structural processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique we applied is extremely reliable and sensitive to measure cortical thickness differences 21 even in submillimeters with improved spatial localization, and uses of more stable structural parameters. 22 Functional and structural plasticity in the so-matosensory cortex have been noticed in rats 23 after altered sensory experience. In humans, a comparable thickening of the SSC at the border between the postcentral gyrus and sulcus has recently been reported in chronic stroke patients when compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, axonal sprouting in central (Darian-Smith and Gilbert, 1994;Florence et al, 1998) and peripheral (Darian-Smith and Brown, 2000;Darian-Smith, 2004) sensory systems in response to peripheral lesions have been reported. Dendritic reorganization also occurs in response to sensory denervation (Hickmott and Steen, 2005).…”
Section: Introductionmentioning
confidence: 99%